2008
DOI: 10.1118/1.3005609
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of the PRESAGE/optical‐CT 3D dosimetry system

Abstract: This work presents extensive investigations to evaluate the robustness (intradosimeter consistency and temporal stability of response), reproducibility, precision, and accuracy of a relatively new 3D dosimetry system comprising a leuco-dye doped plastic 3D dosimeter (PRESAGE) and a commercial optical-CT scanner (OCTOPUS 5x scanner from MGS Research, Inc). Four identical PRESAGE 3D dosimeters were created such that they were compatible with the Radiologic Physics Center (RPC) head-and-neck (H&N) IMRT credential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 17 publications
3
119
0
Order By: Relevance
“…4. Improvements in scanner hardware and acquisition technique 17 ͑improved fluid filtration and RI matching and improved acquisition parameters and prescan correction͒ reduced noise to ϳ2% ͑root mean squared error͒ and edge artefacts ͑4 mm from edge͒ as compared to earlier reports.…”
Section: Iiia Intercomparison Of Presage Dose Ebt Dose and Eclipsmentioning
confidence: 62%
See 3 more Smart Citations
“…4. Improvements in scanner hardware and acquisition technique 17 ͑improved fluid filtration and RI matching and improved acquisition parameters and prescan correction͒ reduced noise to ϳ2% ͑root mean squared error͒ and edge artefacts ͑4 mm from edge͒ as compared to earlier reports.…”
Section: Iiia Intercomparison Of Presage Dose Ebt Dose and Eclipsmentioning
confidence: 62%
“…These include a coplanar open-beam treatment, 3 a highly modulated IMRT treatment, 4 and small field open-beam treatment, respectively. 17 Each verification experiment demonstrated excellent ͑4% dose difference and 4 mm DTA͒ agreement of Presage dose measurement with independent planar EBT film measurements as well as 3D dose calculations from the TPS after normalization ͑i.e., relative dose measurement͒. The present work, investigating the feasibility of relative dosimetry in a credentialing phantom represents a natural extension of these efforts.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a promising new radiochromic material, PRESAGE, 223 has been introduced and detailed studies of the basic dosimetric properties have confirmed its promise for 3D dosimetry. 224 Principal advantages include relative insensitivity of dose response to atmospheric exposure and to the nature of radiochromic optical contrast that is light absorbing rather than light-scattering ͑peak OD change is at ϳ633 nm͒. The absorptive nature of the contrast is more amenable to accurate dose read-out by opticalcomputed-tomography optical-CT. [225][226][227] …”
Section: Vb2 Fricke and Radiochromic Gels And Plasticsmentioning
confidence: 99%